Peyton Place - Metalious, Grace (Buccaneer Books, 1994)
The story of a repressive New England town known for its high standards of public morality, and the steamy sexual activities that take place behind its bedroom doors. While the town's rigid mores lead to hypocrisy and repression, the earthy characters have an unbelievably high level of sexual functioning. In this environment, Allison McKenzie, a dreamy girl coming to womanhood, must make her way without a father, living with her frigid mother Constance McKenzie.